Decision-Making and Life Satisfaction: The Role of General Decision-Making Styles and Maximizing Tendency as Predictors - Sari, Meylisa Permata (Humaniora: Journal of Indonesia Culture and Society, 2022)
However, research that focused on testing the role of decision-making on life satisfaction was still limited, even though almost every aspect of human life involves decision-making, and the results could determine one's life situation. There were prior studies that attempted to explore the relationships between life satisfaction and decision-making; however, the results were not conclusive. Therefore, the research aimed to test the relationship between decision-making styles and life satisfaction. Convenience sampling was used in data collection, and 154 university students participated in the research. It used a cross-sectional survey design to test the research hypothesis. The survey consisted of research information, informed consent, demographic, and measuring instrument for research variables. Decision-making styles are measured using General Decision-Making Styles and Maximizing Scale. Life satisfaction was measured using the Satisfaction with Life Scale. The result of multiple linear regression analysis shows that rational decision-making style and tendency to satisfice significantly predict higher levels of life satisfaction, while spontaneous decision-making style and tendency to maximize predict lower levels of life satisfaction. On the other hand, intuitive, dependent, and avoidant decision-making styles do not significantly predict life satisfaction. The implication and direction for future research are discussed.Â